Cereals prospects in India to 2020: implications for policy - Kumar, Praduman; Rosegrant, Mark W.; Hazell, Peter B. R. (International Food Policy Research Institute, 1995)
Achieving food security has been the overriding goal of agricultural policy in India. The introduction and rapid spread of high-yielding rice and wheat varieties in the late 1960s and early 1970s resulted in steady output growth for foodgrains. Public investment in irrigation and other rural infrastructure and research and extension, together with improved crop production practices, has significantly helped to expand production and stocks of foodgrains. However, concern is increasing that the rapid growth from the Green Revolution is waning. Public investments in agriculture are declining, and the annual increment to gross capital formation in agriculture is now lower than in the early 1980s. In the years to come, higher economic growth as well as sizable population growth will increase the demand for food. The structure of demand is also changing, as diets are diversifying from the basic cereal staples to fruits, vegetables, and other higher-valued foods. Collaborative research between the Indian Agricultural Research Institute (IARI) of the Indian Council for Agricultural Research and the International Food Policy Research Institute (IFPRI) has explored how these possibly conflicting trends in supply and demand will affect net trade in grains in India, and it suggests policies for meeting the growing demand.